NEW PERSPECTIVES ON SUBJECTS WHO BECOME ILL IN HOSPITAL WORK - Silmar Maria Silva; Patrícia Campos Pavan Baptista (Universidade Federal do Paraná, 2013)
This article aims to reflect on the new ways of viewing those subjects who become ill in hospital work, evidencing qualitative phenomenological research's potential for understanding not only the illness, but also the subject who falls ill. Falling ill in hospital work has been shown to be a complex phenomenon, requiring studies which consider diverse aspects and which can understand the everyday of work relationships and the experiences of the subjects who become ill. Becoming aware of the impact of becoming ill at work and valuing the subject and the experience lived through means delineating new ways of intervening in the worker's health, minimizing harm and understanding the worker in his or her existential totality.